(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND AND AIMS The widely used Pitt Bacteraemia Score (PBS) has repeatedly been described as a risk factor for short-term mortality in Staphylococcus aureus bloodstream infection (BSI), but little is known about its overall predictive performance. We therefore aimed to externally validate the PBS in S. aureus BSIs. METHODS We performed a retrospective validation study at the University Hospital Basel. Adult patients with a first episode of methicillin-susceptible S. aureus BSI between January 2008 and December 2013 were eligible for the study. We measured the overall discriminative power of the PBS at day of BSI onset in predicting 30-day all-cause mortality by receiver-operating characteristics analysis. For each PBS cut-off, we calculated the corresponding sensitivity, specificity and predictive values for prediction of 30-day all-cause mortality. RESULTS A total of 329 patients were included in the final analysis: The median PBS at BSI onset was 0 (interquartile range, 0–2) with patients suffering from various comorbidities (Charlson Comorbidity Index median 3, interquartile range 1–5). Thirteen percent of patients (43/329) died within 30 days from any cause. At BSI onset, 52% (170/329) of patients had a PBS of zero; the concomitant specificity and positive predictive value for prediction of 30-day all-cause mortality were 0% and 13%, respectively. The overall performance of the PBS in predicting the 30-day all-cause mortality was lower than published, with an area under the curve of 0.711 (95% confidence interval 0.614–0.807; p <0.001). CONCLUSIONS For short-term mortality, the PBS had a low predictive value in a patient population with methicillin-susceptible S. aureus BSI. There is a need to improve simple clinical scores to better predict mortality, in particular for S. aureus.